Endoscopic management of gastrointestinal wall defects, fistula closure, and stent fixation using through-the-scope tack and suture system - Krishnan, Arunkumar; Shah-Khan, Sardar M.; Hadi, Yousaf; Patel, Neel; Thakkar, Shyam; Singh, Shailendra (Endoscopy, 2023)
Background Multiple devices are available for tissue approximation. A new through-the-scope suturing (TTSS) device has recently been introduced; however, data on its scope of use and clinical effectiveness are limited. We aimed to assess the clinical course and effectiveness of this TTSS device.Methods A retrospective review was performed for consecutive patients who underwent TTSS application. Primary outcomes were technical and clinical success, and secondary outcomes included adverse events and long-term clinical success.Results 53 patients (mean age 67.8 years; 69.8 % females) were included, with a mean defect size of 32.6 mm (SD 11.9). Technical success was achieved in 51 patients (96.2 %). Clinical success was achieved in 49 patients (92.4 %). Two patients (3.8 %) experienced failed fistula closure after technical success. Long-term follow-up (> 30 days) was available for 45 patients (84.9 %), with a mean follow-up of 7.2 months. One patient (1.9 %) had self-reported bleeding that did not require further intervention.Conclusions TTTS was an effective and safe method for the closure of large gastrointestinal defects and could be used for fistula closure and stent fixation, making it a valuable addition to the armamentarium of endoscopic closure devices.